Interferensi Fonologis Bahasa Sunda dalam Bahasa Indonesia oleh Penutur Sunda di Media Sosial YouTube - , SITI MASITOH; , Drs. Ariyanto, M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Language is an instrument in communicating between a same or two different speech community. This research will discussed about difference of phonological system between Sundanese language with Indonesian language. That matter help to explain Sundanese phonological interference in Indonesian language especially in the scope social media YouTube. Data collection method that used is downloading and scrutinize method by recording technique as first step. Nonparticipation observation and noted technique used as subsequent technique. Analyze method which used in this research is phonetic articulator method, orthography method, and comparison method. The theory that is used for the analysis is sociolinguistics theory (concerned interference and cause of interference) and phonology theory (concerned phonological changes). This Sundanese phonological interference in Indonesian language at the scope social media YouTube strung out phonological changes as, umlaut seperti phonological replacement of [ï«] becomes[ï©] at sabotase [sabotasï«] becomes sabotaseu [sabotasï©], assimilation like phonological changes [f] becomes [p] at [fakta] becomes [pakta], permutation like location movement of cluster [pr] and [kr] as pronounciation of [prosedUr] becomes [porsedUr].